Aerodynamic stability of road vehicles in dynamic motion - Okada, Yoshihiro; Cheng, See Yuan; Tsubokura, Makoto; Nakashima, Takuji; Nouzawa, Takahide (2013)
A method for dynamic coupling simulation of flow and vehicle motion was developed based on large eddy simulation technique with moving boundary methods. The method was applied to investigated the aerodynamic stability of vehicle under a transient driving situation. A coefficient to quantify the aerodynamic damping was defined. For the sedan-type, simple body models investigated, the underbody provides the highest proportion of aerodynamic damping. However, it is the trunk deck contribution that causes the different damping magnitudes in the models with distinct A- and C-pillar geometrical configurations.